2006
DOI: 10.1111/j.1365-2788.2006.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Community and cluster centre residential services for adults with intellectual disability: long‐term results from an Australian‐matched sample

Abstract: Both cluster centre and dispersed community living offer lifestyle and skill development advantages compared with opportunities available in large residential institutions. Dispersed community houses, however, offer increased opportunities for choice-making, acquisition of adaptive behaviours and improved life quality for long-term institutionalized adults with IDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 20 publications
3
46
0
4
Order By: Relevance
“…U dve studije je ustanovlјeno pogoršanje problema u ponašanju, koja nisu bila statistički značajna, dok se u preostalim studijama nije pokazala značajna promena. Pojedini autori su istakli da su, iako je nivo problematičnog ponašanja ostao isti, otkrili promene u prirodi problematičnog ponašanja nakon preselјenja iz institucije u otvorenu zajednicu (Young, & Ashman, 2004;Golding, Emerson, & Thornton, 2005;Young, 2006). Suprotno ovim tvrdnjama, Simons ističe da postoji bitna razlika između faktora koji utiču na ispolјavanje problema u ponašanju i onih koji su potrebni da se takvo ponašanje održi i tvrdi da faktori sredine mogu uticati na učestalost i izraženost problema u ponašanju (Symons, 2005).…”
Section: Diskusijaunclassified
“…U dve studije je ustanovlјeno pogoršanje problema u ponašanju, koja nisu bila statistički značajna, dok se u preostalim studijama nije pokazala značajna promena. Pojedini autori su istakli da su, iako je nivo problematičnog ponašanja ostao isti, otkrili promene u prirodi problematičnog ponašanja nakon preselјenja iz institucije u otvorenu zajednicu (Young, & Ashman, 2004;Golding, Emerson, & Thornton, 2005;Young, 2006). Suprotno ovim tvrdnjama, Simons ističe da postoji bitna razlika između faktora koji utiču na ispolјavanje problema u ponašanju i onih koji su potrebni da se takvo ponašanje održi i tvrdi da faktori sredine mogu uticati na učestalost i izraženost problema u ponašanju (Symons, 2005).…”
Section: Diskusijaunclassified
“…One study by Young in 2006 of people with moderate to severe intellectual disability showed increased adaptive behaviour, choice-making and life quality in a group followed up after discharge from institutional living into a community setting. 6 The corollary has also been studied and Rutter has written extensively on the detrimental effects of institutionalisation. 7,8 The report itself cites a number of studies to support the case for community living both from a quality of life and costeffectiveness point of view.…”
Section: Deinstitutionalisation Is Generally a Good Thingmentioning
confidence: 99%
“…Furthermore, housing is an important determinant of mental health for people with intellectual disabilities (McGlaughlin 2004). A number of studies have addressed the outcome of different types of housing for people with psychiatric disabilities (Hansson et al 2002;Kyle and Dunn 2008;Nelson et al 1998;Oliver and Mohamad 1992) and intellectual disabilities (Emerson 2004;McConkey 2007;Perry and Felce 2003;Young 2006). Studies indicate limitations in community-based housing opportunities for people with psychiatric disabilities and conclude that homelessness is all too commonly experienced by people discharged from hospital wards (Burt et al 2007;Forchuk et al 2006;Kuno et al 2000;Nordentoft et al 1997).…”
Section: Introductionmentioning
confidence: 99%